The Relationship between Education, Knowledge, and Attitudes with The Prevention of COVID-19 in Comorbid Patients at Kuta Alam Public Health Center in Banda Aceh - Safita, Siti Sarah; Husnah, Husnah; Waraztuty, Ika; Kurniawan, Hendra; Andayani, Hafni (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
COVID-19 is in a transitional phase towards becoming endemic, which means individuals with comorbidities are at risk of contracting the disease. On average, individuals who succumb to COVID-19 have at least one comorbidity. Therefore, individuals with comorbidities should be cautious and adhere to health protocols. The research aims to determine the relationship between education, knowledge, attitudes, and COVID-19 prevention among patients with comorbidities at the Kuta Alam Community Health Center in Banda Aceh. This study is observational with a cross-sectional design. Data collection took place from March 2nd to 13th, 2023, involving 100 individuals with comorbidities at the Kuta Alam Community Health Center in Banda Aceh. The research findings indicate that out of 100 individuals with comorbidities, the most common comorbidity is hypertension (60%), with 78% having one comorbidity, and 62% being COVID-19 survivors. Respondents with higher education levels showed that 98.4% made good efforts in preventing COVID-19. Additionally, respondents with good knowledge demonstrated that 93.8% made good preventive efforts, while those with a positive attitude showed 96.9% engagement in preventive measures. The Spearman rank test results at a 95% confidence interval and Î± of 0.05 showed correlations between education, knowledge, and attitudes with COVID-19 prevention among comorbid patients, obtaining respective values of (P value = 0.000, r = 0.871), (P value = 0.000, r = 0.778), and (P value = 0.000, r = 0.847). In conclusion, there exists a strong correlation between education, knowledge, attitudes, and COVID-19 prevention among comorbid patients at the Kuta Alam Community Health Center in Banda Aceh. Higher education levels correspond to better knowledge and favorable attitudes towards COVID-19 prevention among individuals with comorbidities.